2020
DOI: 10.22373/ekw.v6i1.6913
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical Activation Using Base Solution With Various Concentrations Towards Sarulla Natural Zeolite

Abstract: : Material characteristics analysis of Sarulla natural zeolite (SNZ) with base activation has been carried out. The base used was NaOH at various concentrations; 0.2 M, 0.5 M, and 2 M. Base activated catalysts were characterized by X-ray Fluorescence (XRF), X-ray diffractometer (XRD), Fourier-transform Infrared (FTIR) Spectroscopy, Scanning Electron Microscopy (SEM) and gas adsorption analysis using BET method. The procedures applied have caused differences in adsorption and desorption rates as well as the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The surface area of Fe-La/NHZ-1 and Fe-La/NHZ-2 catalyst was lower than parent nano HZSM-5 after the impregnation of metal transition (Fe and La), 294.0965 and 286.7340, respectively. This is in accordance with previous research [15,16]. Based on Table 1, it can be concluded that the particles of metal were successfully filled on the surface and incorporated into nano HZSM-5 pore.…”
Section: Catalyst Characterizationsupporting
confidence: 92%
“…The surface area of Fe-La/NHZ-1 and Fe-La/NHZ-2 catalyst was lower than parent nano HZSM-5 after the impregnation of metal transition (Fe and La), 294.0965 and 286.7340, respectively. This is in accordance with previous research [15,16]. Based on Table 1, it can be concluded that the particles of metal were successfully filled on the surface and incorporated into nano HZSM-5 pore.…”
Section: Catalyst Characterizationsupporting
confidence: 92%
“…Density is one of the physical properties of testing the stability of liquid smoke which is determined by the ratio between weight and sample volume (Sari et al, 2021) . The amount of density is not related to the quality of the liquid smoke but shows the number of components in the liquid smoke (Gea et al, 2020) . Density also shows the density of the liquid molecular bonds in it (Jayanudin et al, 2012) .…”
Section: Liquid Smoke Quality Analysismentioning
confidence: 99%
“…Base treatment of zeolites with intermediate Al contents involves the selective extraction of silicon atoms resulting in a decrease of the Si/Al ratio or increase (case of low Si/Al ratio) and a significant loss of material at high base concentration [24]. Numerous investigations have demonstrated that activating natural zeolites with NaOH can increase crystallinity and the Si/Al ratio in catalysts at low concentrations such as 0.2 M [25]. The presence of the weak, medium and strong acid sites in zeolite altered the Si/Al ratio, which depends on the NaOH solution concentration and the zeolite composition [26].…”
Section: ■ Introductionmentioning
confidence: 99%